2014
DOI: 10.5846/stxb201303010328
|View full text |Cite
|
Sign up to set email alerts
|

Changes in land use and soil and water conservation of the upper and middle reaches of Heihe river basin during 2000–2010

Abstract: Based on Landsat TM / ETM image data and some other survey materials, this paper analyzed the land use change in the upper and middle reaches of Heihe river basin during 2000-2010. Subsequently, two prominent functions of ecosystem service: water conservation and soil retention were evaluated, from upstream, midstream, as well as the whole region. The findings of this study are summarized as following: (1) The main types of land use is unused land accounting for more than 60% of the total area. In recent ten y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The bare area decreased from 75318 km 2 in 2000 to 74490 km 2 in 2010. The results coincided with the change analysis result of Liu et al[7]. Only one difference was occurred in the grass land.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The bare area decreased from 75318 km 2 in 2000 to 74490 km 2 in 2010. The results coincided with the change analysis result of Liu et al[7]. Only one difference was occurred in the grass land.…”
supporting
confidence: 90%
“…The reason was likely that the water conservation function of the forest in the upstream made the previous storage soil water becoming another contribution approach on ET. Liu et al [7] reported that the water storage by the soil increased by 56.5% (1.625*10 8 tons in 2000 to 2.568*10 8 tons). The forest in the midstream may use the ground water because of the deeper root depth.…”
Section: Correlation Analysis Between Et and Climate Factorsmentioning
confidence: 99%
“…The ecosystem service value assessment should be carried out as soon as possible. In China, the ecosystem service values of large-scale basins all have been evaluated Wu et al 2009;Hou et al 2013;Bai et al 2011;Liu et al 2014). So, it is necessary to evaluate the ecosystem service change of the Nenjiang River Basin to constitute accurate policy for sustaining development.…”
Section: Introductionmentioning
confidence: 99%